In-the-loop validation of fuel cell vehicle control. (5th October 2011) - Wilhelm, Erik; Fowler, Michael; Fraser, Roydon A.; Stevens, Matthew
Advanced powertrain development is accelerated with increased safety using model-based design tools and in-the-loop validation. The effective application of a 'Hardware-in-the-Loop' (HIL) and 'Software-in-the-Loop' (SIL) simulation system for the development of the safety and hybrid control algorithms for a hydrogen fuel cell hybrid passenger vehicle are described in this work. Models of the powertrain subsystems are assembled from vehicle test data. SIL simulation is used to test initial code integrity and to validate the HIL vehicle models. Battery charging control and hybrid control strategies are tested in HIL and the results are then validated in real-world application.